Tuberculosis drug streptomycin as a potential cancer therapeutic: inhibition of miR-21 function by directly targeting its precursor - Bose, Debojit; Jayaraj, Gopal Gunanathan; Suryawanshi, Hemant; Agarwala, Prachi; Pore, Subrata Kumar; Banerjee, Rajkumar; Maiti, Souvik (Angewandte Chemie-International Edition, 2012)
Keywords: Apoptosis; drug discovery; Gene expression; inhibitors; RNA

Tale of RNA G-quadruplex - Agarwala, Prachi; Pandey, Satyaprakash; Maiti, Souvik (Organic & Biomolecular Chemistry, 2015)
G-quadruplexes are non-canonical secondary structures found in guanine rich regions of DNA and RNA. Reports have indicated the wide occurrence of RNA G-quadruplexes across the transcriptome in various regions of mRNAs and non-coding RNAs. RNA G-quadruplexes have been implicated in playing an important role in translational regulation, mRNA processing events and maintenance of chromosomal end integrity. In this review, we summarize the structural and functional aspects of RNA G-quadruplexes with emphasis on recent progress to understand the protein/trans factors binding these motifs. With the revelation of the importance of these secondary structures as regulatory modules in biology, we have also evaluated the various advancements towards targeting these structures and the challenges associated with them. Apart from this, numerous potential applications of this secondary motif have also been discussed.

Targeting RNA G-Quadruplexes for potential therapeutic applications - Pandey,Satyaprakash; Agarwala, Prachi; Maiti,Souvik (Topics in Medicinal Chemistry, 2017)
RNA G-quadruplexes are non-canonical structures formed in G-rich regions of transcriptome. Considerable research points towards the potential role for these dynamic structures in various genes involved in multiple pathways. The ability of these structures to influence important biological processes has been demonstrated in few selected important genes and more recently in a global manner across the transcriptome. RNA G-quadruplexes are implicated in fundamental processes such as translational regulation, alternative splicing, mRNA transport and telomere homeostasis to name a few. The involvement of these structures in key biological processes makes them attractive targets for therapeutic interventions. Here we discuss the structural features of RNA G-quadruplex that make it more monomorphic to develop ligands unlike the polymorphic DNA G-quadruplexes. Furthermore, the role of RNA G-quadruplexes in important genes involved in diseases and disorders such as neurodegeneration, cancer and viral infections has been highlighted. A summary of ligands and their established roles in targeting RNA G-quadruplex structures has been discussed in context of important processes. Moreover, we highlight the need to develop ligands that are highly specific in targeting RNA G-quadruplexes, a new target to restore homeostasis in dysregulated conditions.